MXene-Based Aptasensor: Characterization and High-Performance Voltammetry Detection of Deoxynivalenol - Sangu, S.S. (Springer, 2021)
Deoxynivalenol (DON) is a mycotoxin secreted by Fusarium species members, and the consumption of which causes a serious health issue. In this work, MXene is used to generate a highly sensitive and selective biosensing system for DON. MXene is prepared by the selective etching of aluminum from titanium aluminum carbide (Ti3AlC2-MAX) powder using hydrochloric acid-lithium fluoride (HCl-LiF). The prepared MXene surface is immobilized with a tailor-made DON aptamer, and its affinity towards DON is measured using a sweep voltammetry. Field emission scanning electron microscopy (FESEM) displays the intercalation between MXene layers indicating the successful etching of aluminum. Energy-dispersive X-ray spectroscopy study confirms the incident elemental compositions, whereas X-ray photoelectron spectroscopy analysis shows a high composition of Ti-Fx and TiO2, due to the replacement of the aluminum layers with oxygen and fluorine terminations. The presence of oxygen is beneficial for surface modification and biomolecular immobilization as attested by the Fourier-transform infrared spectroscopy peak profile. The aptasensor shown here has a high sensitivity with a limit of detection at 1 fg mLâ1 and demonstrates a remarkable selectivity towards DON by discriminating the binding of similar mycotoxins, zearalenone, and ochratoxin A and with DON-spiked paddy extract. This simple yet cost-effective high-performance detection of DON can be an alternative strategy for screening food and feed samples. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.